ATM/Wip1 activities at chromatin control Plk1 re-activation to determine G2 checkpoint duration - Jaiswal, Himjyot; Benada, Jan; Müllers, Erik; Akopyan, Karen; Burdova, Kamila; Koolmeister, Tobias; Helleday, Thomas; Medema, René H; Macurek, Libor; Lindqvist, Arne (The EPMA journal, 2017)
After DNA damage, the cell cycle is arrested to avoid propagation of mutations. Arrest in G2 phase is initiated by ATM-/ATR-dependent signaling that inhibits mitosis-promoting kinases such as Plk1. At the same time, Plk1 can counteract ATR-dependent signaling and is required for eventual resumption of the cell cycle. However, what determines when Plk1 activity can resume remains unclear. Here, we use FRET-based reporters to show that a global spread of ATM activity on chromatin and phosphorylation of ATM targets including KAP1 control Plk1 re-activation. These phosphorylations are rapidly counteracted by the chromatin-bound phosphatase Wip1, allowing cell cycle restart despite persistent ATM activity present at DNA lesions. Combining experimental data and mathematical modeling, we propose a model for how the minimal duration of cell cycle arrest is controlled. Our model shows how cell cycle restart can occur before completion of DNA repair and suggests a mechanism for checkpoint adaptation in human cells.
Keywords: biologické modely; posttranslační úpravy proteinů; buněčné linie; teoretické modely; kontrolní body fáze G2 buněčného cyklu; proteinfosfatasa 2C; Repressor Proteins; represorové proteiny; Chromatin; lidé; Models, Biological; Protein Serine-Threonine Kinases; Protein Processing, Post-Translational; protoonkogenní proteiny; ATM protein; mapování interakce mezi proteiny; Cell Line; Cell Cycle Proteins; Protein Interaction Mapping; fosforylace; chromatin; Proto-Oncogene Proteins; G2 Phase Cell Cycle Checkpoints; Fluorescence Resonance Energy Transfer; Ataxia Telangiectasia Mutated Proteins; Protein Phosphatase 2C; proteiny buněčného cyklu; rezonanční přenos fluorescenční energie; Models, Theoretical; protein-serin-threoninkinasy; Phosphorylation; Humans